MENEGUHKAN TUJUAN DAN BIDANG KAJIAN SOSIOLOGI PENDIDIKAN ISLAM SEBAGAI BASIS INOVASI SOSIAL - Rahmah, Fiska; Nurbaya, Siti; Irfan, Muhammad (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STIT Sunan Giri Bima, 2024)
This study discusses the objectives and scope of Islamic educational sociology, emphasizing its relevance to the process of individual personality formation and social dynamics. Islamic educational sociology is viewed as a discipline that not only studies social interactions in the context of education but also integrates Islamic ethical and spiritual values as the foundation for student development. The research method used is a literature study by examining various relevant literature, such as books, articles, and scientific journals. The results of the study show that Islamic educational sociology plays an important role in the process of socialization, analysis of social development, and the adjustment of educational institutions to changes in society, both in terms of demographics, technology, and culture. In addition, Islamic education through a sociological approach is expected to produce a generation that is faithful, knowledgeable, and contributes positively to social development. Thus, Islamic educational sociology not only functions as an academic tool but also as an instrument of social transformation in line with Islamic values.